Simultaneous Optimization of Block Replacement and Spare Part Ordering Time for a Multi Component System with Separate Spare Part Ordering for Block and Failure Replacements - Mardin, Farid; Dekker, Rommert (Journal of Engineering and Technological Sciences, 2016)
A block replacement schedule can be optimized simultaneously with a spare parts ordering schedule, since all items are replaced at a constant interval. The solution of joint optimization for spare parts ordering time and block replacement gives lower costs compared to separate optimization of ordering time and replacement time. The spare parts for replacement can be classified as stochastic demand for failure replacement and deterministic demand for block replacement. In this paper, we propose a simulation model for a separate spare parts ordering schedule. The solution was compared to the solution for a model with common spare parts for both failure and block replacement. The system has N identical components, each with a Weibull lifetime distribution. The costs of failure and block replacements, and also the costs of ordering, holding and shortage of spare parts are given. The proposed model was shown to perform better than the common order model. Also, compared to the age replacement model, the solution of the proposed model is relatively similar, yet the economies of scale would be an advantage for the block replacement over age replacement.